Questão social no Brasil: uma análise sobre o debate nas décadas de 1920 e 1930 - Barbosa, Aline Ramos (2011)
The transition to modernity in Brazil has its roots in the transformations engendered in Brazilian society since the mid-nineteenth century to the emblematic 1930 s Revolution. The social question, that in this context was related to capital-work conflict engedered by the economic changes occurred in the country, may has its solution take as part of universal rights generation, specifically, with reference to social rights. In Brazilian case, that don t seeks the marshallian logic, first came the social rights, in the decade of 1930, concomitantly with the suppression of political rights and strong reduction of civil rights (come and go) by varguista State. Notwithstanding, despite the evident importance of the decade of 1930 in this process, it can t be underestimated the importance of the previous years. Thus, the focus of this research is analyze the advances and continuities in relation to social question in Brazil, that, despite to be a problem always present in this country, when referred to work question, found in the decade of 1930 a solution supported in work and welfare legislations and its and cultminating in 1934 s Constitution, in the chapter referred to Social and Economic Order. That way, the question of police became a social issue, to acquire the status of political issue in the 1934 s Constitution.